IMPACT OF FINANCIAL RATIOS ON THE SHARE PRICE OF A CONSUMER GOODS INDUSTRY COMPANY - Aurora Angela; Endah Purnama Sari; Livia Yonathan (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2022)
It is essential that investors have proper financial knowledge for each of their business decisions. One of the ways is to achieve it is to conduct a fundamental analysis related to the financial ratios, which can have an effect on the share price. The purpose of the particular research is to analyse earnings per share (EPS), price to earnings ratio (PER), price to book value (PBV), debt to equity ratio (DER), return to equity (ROE) and their effects on the price of the stock. The particular research is conducted on a consumer goods industry company enlisted in IDX between 2018 and 2020. The test of research hypothesis is conducted utilising multiple linear regression. The outcome of research is that EPS and PBV play a significant role in the share price, whereas PER, DER, ROE are the other way around.